Henoch–Schönlein purpura and systemic disease in children: retrospective study of clinical findings, histopathology and direct immunofluorescence in 34 paediatric patients. (25th February 2015) - Johnson, E.F.; Lehman, J.S.; Wetter, D.A.; Lohse, C.M.; Tollefson, M.M.
Summary Background Henoch–Schönlein purpura (HSP), an IgA‐mediated small vessel vasculitis, is the most common form of vasculitis in children. HSP is commonly associated with systemic involvement of the gastrointestinal tract, joints and kidneys. Renal involvement is the main cause of morbidity and mortality in HSP. Objectives To characterize the clinical, histopathological and direct immunofluorescence (DIF) findings, and to correlate the findings with systemic disease in 34 children with HSP seen at our institution. Methods This was a retrospective review of paediatric patients with HSP and with available biopsy specimens seen at our institution between 1993 and 2013. Results Thirty‐four paediatric patients were identified (mean age 10·7 years). Renal involvement was found in 17 (50%) patients, gastrointestinal tract involvement in 22 (65%) and joint involvement in 23 (68%). Renal involvement was significantly associated with papillary dermal oedema on histopathology (P < 0·01) and the presence of perivascular C3 on DIF (P = 0·01). The presence of lesions above the waist was significantly associated with gastrointestinal involvement (P = 0·03), as was the presence of clinically apparent oedema (P = 0·01). Conclusions This study suggests that in children with HSP, microscopic dermal oedema and C3 on DIF may be predictive of renal involvement. Patients with clinically apparent oedema and lesions above the waist are more likely to have gastrointestinal involvement.